Food and drug reactions, wheezing, and eczema in preterm infants. Issue 4 (April 1990) - Lucas, A; Brooke, O G; Cole, T J; Morley, R; Bamford, M F
Abstract : Allergic reactions were investigated in 777 preterm infants who were randomly assigned to early diet and followed up to 18 months post term. Wheezing or asthma was common (incidence 23%); it was associated with neonatal ventilation, maternal smoking, and a family history of atopy and was unexpectedly reduced in babies born by caesarean section. Even in non-ventilated infants, the incidence of subsequent wheezing was 18%, rising to an estimated 44% (using logistic regression) when the foregoing risk factors (excluding ventilation) were present. Eczema occurred in 151 infants (19%) and was strongly associated with multiple pregnancy (30% incidence in twins or triplets). Reactions to cows' milk (incidence: 4.4% from detailed history; 0.8% confirmed by challenge), other foods (10%), and drugs (5%) were within the range reported in full term infants. Milk and food reactions were associated with multiple pregnancy (19%) and a family history of atopy. Reactions to drugs were least likely to occur in infants who had been ventilated and were on multiple medications in the neonatal period, suggesting that drug tolerance may have developed. We speculate that preterm infants may be a high risk group for asthma and eczema, which could imply an association between atopy and prematurity.